2017
DOI: 10.1136/neurintsurg-2016-012903
|View full text |Cite
|
Sign up to set email alerts
|

Patency of the vein of Labbé after venous stenting of the transverse and sigmoid sinuses

Abstract: In the majority of venous stenting cases involving the transverse and sigmoid sinuses, the VOL remains widely patent. Complete VOL occlusion rarely occurs after stenting and may not result in clinical sequelae. Stent coverage of the VOL should not deter the therapeutic use of venous sinus stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…In 2017, Raper et al 6 reported a 25% incidence of impaired VOL flow immediately following VSS. The reported 25% incidence is based on 32 patients with post-stent arteriography, which constitutes only 57% of the cohort of patients with VSS, as the remaining 43% were lacking control arteriography following VSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Raper et al 6 reported a 25% incidence of impaired VOL flow immediately following VSS. The reported 25% incidence is based on 32 patients with post-stent arteriography, which constitutes only 57% of the cohort of patients with VSS, as the remaining 43% were lacking control arteriography following VSS.…”
Section: Discussionmentioning
confidence: 99%
“…Levitt et al 5 reported no immediate occlusions of the VOL after VSS. In contradistinction, Raper et al 6 reported abnormal findings in the VOL after VSS in 25% of patients immediately post-treatment and in 28% of patients at the 3 month follow-up (26% diminished caliber and 2% prolonged transit time).…”
Section: Introductionmentioning
confidence: 94%
“…There is an expanding body of literature on stenting of intracranial venous sinuses for a range of indications (24)(25)(26)(27)(28)(29)(30)(31)(42)(43)(44)(45)(46)(47). This literature exposes the possible risks of intracranial stenting, particularly in-stent thrombosis, and provides strategies for prevention of these complications, namely anticoagulation and antiplatelet therapy.…”
Section: Stent Safety: Lessons From Venous Sinus Stentingmentioning
confidence: 99%
“…Greater experience exists with stenting of the transverse sinuses for the treatment of idiopathic intracranial hypertension (24)(25)(26)(27)(28)(29)(30)(31). According to recent systematic reviews, the overall complication rate associated with this intervention, including minor complications such as wound hematomas or pseudoaneurysms, is 1-7% (24)(25)(26)(27)(28)(29).…”
Section: Stent Safety: Lessons From Venous Sinus Stentingmentioning
confidence: 99%
See 1 more Smart Citation